1976
DOI: 10.1017/s002211207600311x
|View full text |Cite
|
Sign up to set email alerts
|

Axially symmetric turbulent boundary layers on cylinders: mean velocity profiles and wall pressure fluctuations

Abstract: Experimental measurements of the mean velocity profiles produced by axially symmetric turbulent boundary layers on cylinders of various diameters are described. The profile measurements were made with very small hot wires developed for this investigation. Measurements of the wall shear stress on cylinders ranging from 0.02 to 2.0 in. in diameter are also reported. In the boundary layer on cylinders, well-defined regions exist in which the two-dimensional law of the wall and a three-dimensional wake law are val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 16 publications
(37 reference statements)
11
90
1
1
Order By: Relevance
“…The smaller slope is however consistent with the experimental results in Willmarth et al (1976). As the r i /r o ratio gets smaller, experimental (Willmarth et al (1976)) and DNS results (Chung et al (2002), Boersma and Breugem (2011)) indicate that the slope will decrease further. Figure 4 displays the sensitivity of the force power spectral density, which will be defined in Section 5, to the grid density.…”
Section: Sensitivity Of the Mean Velocity Profilesupporting
confidence: 80%
“…The smaller slope is however consistent with the experimental results in Willmarth et al (1976). As the r i /r o ratio gets smaller, experimental (Willmarth et al (1976)) and DNS results (Chung et al (2002), Boersma and Breugem (2011)) indicate that the slope will decrease further. Figure 4 displays the sensitivity of the force power spectral density, which will be defined in Section 5, to the grid density.…”
Section: Sensitivity Of the Mean Velocity Profilesupporting
confidence: 80%
“…In this study we assume that when comparing the response of microphone pairs, the spanwise spacing of the microphones is the primary effect, while the axial spacing of microphones is secondary in importance based on the following arguments. First, Willmarth and coworkers 6,8 found that even for the maximum axial separation in our study, x ϭ1.65␦*, the maximum cross-correlation between axiallyspaced microphones for ␦/aϭ2 and 4 was nearly 0.5. Even higher correlations resulted for smaller axial separations.…”
Section: Methodsmentioning
confidence: 99%
“…Small Preston tubes have been shown to provide accurate measurements of the wall shear stress on a cylinder based on a flat plate calibration. 6,27 The wall shear stress measured using the Preston tubes varied by less than 2.5% from the mean indicating that the boundary layer was essentially axisymmetric. The streamwise mean velocity profile in the boundary layer measured using a hot wire was slightly fuller than predicted by the cylindrical log law of Lueptow et al, 30 but it was within the expected range of variation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations